A Localized Tolerance in the Substrate Specificity of the Fluorinase Enzyme enables "Last‐Step" 18F Fluorination of a RGD Peptide under Ambient Aqueous Conditions1. Issue 34 (2nd July 2014) - Thompson, Stephen; Zhang, Qingzhi; Onega, Mayca; McMahon, Stephen; Fleming, Ian; Ashworth, Sharon; Naismith, James H.; Passchier, Jan; O'Hagan, David
Abstract A strategy for last‐step 18F fluorination of bioconjugated peptides is reported that exploits an "Achilles heel" in the substrate specificity of the fluorinase enzyme. An acetylene functionality at the C‐2 position of the adenosine substrate projects from the active site into the solvent. The fluorinase catalyzes a transhalogenation of 5′‐chlorodeoxy‐2‐ethynyladenosine (ClDEA) to 5′‐fluorodeoxy‐2‐ethynyladenosine (FDEA). Extending a polyethylene glycol linker from the terminus of the acetylene allows the presentation of bioconjugation cargo to the enzyme for 18F labelling. The method uses an aqueous solution (H218O) of [18F]fluoride generated by the cyclotron and has the capacity to isotopically label peptides of choice for positron emission tomography (PET).